Do downward private transfers enhance maternal labor supply? Evidence from around Europe - Ralitza Dimova; François-Charles Wolff (Institute for the Study of Labor (IZA), 2006)
Drawing on a theoretical model of downward private transfers with endogenous labor supply and recursive econometric models based on 2317 mother-daughter pairs from the 2003 SHARE data on 10 European countries, we investigate the impact of private transfers on the career choices of transfer-receiving young mothers. For Europe as a whole, we find a strong positive impact of grandchild care on the labor force participation decision of the mother, but no clear impact of either grandchild care or monetary transfers on the mother's degree of labor market involvement. The link between family transfers and labor supply exhibits an interesting pattern across institutional settings. Finally, while both recipients and donors with better endowments are more likely to participate in a monetary transaction, time transfers are such that mothers with lower level of human capital tend to assist the professional development of their better endowed daughters.
urn:nbn:de:101:1-2008060674
Keywords: 330